2018
DOI: 10.1002/cbin.10959
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen reduces cell proliferation through inhibiting Wnt/β catenin signaling pathway in gastric cancer stem cells

Abstract: Nowadays, most studies focused on cancer stem cells (CSCs) through their abilities to cause tumorigenicity, drug resistance, and cancer recurrence. On the other side, nonsteroidal anti-inflammatory drugs (NSAIDs) have been taken into consideration because of cheapness and availability. For the reasons mentioned above, we have studied the effect of ibuprofen as an NSAID on CSCs derived from AGS and MKN-45 gastric cancer cell lines to perform effective cancer therapy. We evaluated cell viability, spheroid body f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…There is emerging evidence that ibuprofen may in certain specific situations act as an endocrine disrupter [118,119]. The role of ibuprofen in cancer is currently being discussed in the literature, because ibuprofen offers antiproliferative benefits in some situations [120][121][122]. Thus, the discussion about infection and ibuprofen is not surprising as we continue to learn more about this molecule in specific settings with specific patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence that ibuprofen may in certain specific situations act as an endocrine disrupter [118,119]. The role of ibuprofen in cancer is currently being discussed in the literature, because ibuprofen offers antiproliferative benefits in some situations [120][121][122]. Thus, the discussion about infection and ibuprofen is not surprising as we continue to learn more about this molecule in specific settings with specific patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…[36] In the A2780 cell line, ac oncentration of 100 mm for the [Ibu]-ILs and precursor salts was chosen due to the effect of ibupro-fen on the WNT/b-catenin pathway that affects the proliferation of these cells. [37][38][39][40] With the exception of [C 16 Pyr][Ibu] for both cell lines and [N 1,1,2,2OH1 ][Ibu] for A2780 tumorc ells, no cytotoxic effect was observed when exposed for 48 ht oe ach compound (in comparison with Na[Ibu]; Figure 2). Interestingly, for both cell lines, the cytotoxicity of [C 16 Pyr][Ibu] might be attributed to its cation, as [C 16 Pyr]Cl displayed IC 50 values of < 100 and 2.2 AE 0.1 mm for fibroblasts andA 2780 cells, respectively ( Figure 2A and Table 2).…”
Section: ) Melting (T M ) Crystallization (T C ) and Cold Crystallmentioning
confidence: 99%
“…CASK, which has been intensively studied in neurons, is deemed to be an important histone protein in cortical networks and may be involved in the establishment and maintenance of synaptic connections [41][42][43][44]. The role of CASK in carcinoma has been reported only in oesophageal cancer, gastric cancer and colorectal cancer [45,46]. Wang et al found that CASK expression in oesophageal cancer was upregulated at the mRNA and protein levels [39].…”
Section: Discussionmentioning
confidence: 99%